Global inflation dynamics in the post-crisis period: What explains the twin puzzle? - Christian Friedrich (Bank of Canada, 2014)
Inflation dynamics in advanced countries have produced two consecutive puzzles during the years after the global financial crisis. The first puzzle emerged when inflation rates over the period 2009-11 were consistently higher than expected, although economic slack in advanced countries reached its highest level in recent history. The second puzzle - still present today - was initially observed in 2012, when inflation rates in advanced countries were weakening rapidly despite the ongoing economic recovery. This paper specifies a global Phillips curve for headline inflation using inflation expectations by professional forecasters and a measure of economic slack at the global level over the period 1995q1- 2013q3. Phillips curve data points in the period after the global financial crisis show a significantly different but consistent pattern compared to data points in the period before or during the crisis. In the next step, potential explanatory variables at the global level are assessed regarding their ability to improve the in-sample fit of the global Phillips curve. The analysis yields three main findings. First, the standard determinants can still explain a sizable share of global inflation dynamics. Second, household inflation expectations are an important addition to the global Phillips curve. And third, the fiscal policy stance helps explain global inflation dynamics. When taking all three findings into account, it is possible to closely replicate global inflation dynamics over the post-crisis period. – – La dynamique de l'inflation au sein des pays avancés a donné lieu à deux énigmes, qui se sont succédé après la crise financière mondiale. La première apparaît au moment où, de 2009 à 2011, les taux d'inflation étaient systématiquement plus élevés que prévu tandis que le niveau des capacités excédentaires atteignait, de mémoire récente, un sommet. La seconde énigme persiste à ce jour : malgré la reprise, l'inflation connaît un affaiblissement rapide pour la première fois en 2012. Dans son étude, l'auteur spécifie tout d'abord une courbe de Phillips mondiale de l'inflation nominale en s'appuyant sur les anticipations d'inflation de prévisionnistes professionnels, ainsi qu'une mesure des capacités excédentaires à l'échelle internationale pour la période allant du 1er trimestre 1995 au 3e trimestre 2013. Après la crise, les points de données de la courbe présentent une forme homogène sensiblement différente de la forme épousée avant ou pendant la crise. L'auteur évalue ensuite l'aptitude de plusieurs variables explicatives à améliorer l'adéquation statistique sur l'échantillon pour la spécification choisie de la courbe de Phillips. De son analyse se dégagent trois conclusions importantes. 1) Les déterminants habituels permettent encore d'interpréter une bonne partie de la dynamique de l'inflation à l'échelle internationale. 2) Les anticipations d'inflation des ménages sont un apport important à la courbe de Phillips mondiale. 3) L'orientation de la politique budgétaire aide à expliquer le comportement de l'inflation dans le monde. La prise en compte de ces trois observations rend possible une reproduction plus fidèle de la dynamique de l'inflation dans l'après-crise.
Keywords: E31; E5; F41; 330; Inflation and prices; International topics; Fiscal policy